Cancer medicines on the WHO Model List of Essential Medicines: processes, challenges, and a way forward. Issue 12 (December 2022) - Jenei, Kristina; Aziz, Zeba; Booth, Christopher; Cappello, Bernadette; Ceppi, Francesco; de Vries, Elisabeth G E; Fojo, Antonio; Gyawali, Bishal; Ilbawi, Andre; Lombe, Dorothy; Sengar, Manju; Sullivan, Richard; et al.
Summary: The selection of cancer medicines for national procurement requires deliberate evaluation of population benefit, budget impact, sustainability, and health system capacity. However, this process is complicated by numerous challenges, including the large volume and rapid pace of newly developed therapies offering marginal gains at prohibitively high prices. The WHO Model List of Essential Medicines (EML) and Model List of Essential Medicines for Children (EMLc) have undergone a series of evidence-based updates to ensure recommended cancer medicines offer meaningful clinical benefit. This Health Policy paper describes how cancer medicines are listed on the EML and EMLc, including two updated WHO processes: (1) the formation of the Cancer Medicines Working Group, and (2) additional selection principles for recommending cancer medicines, including a minimum overall survival benefit of 4–6 months with improvement to quality of life compared with standard treatment. These updates, along with proposals to include formal price considerations, additional selection criteria, and multisectoral collaboration (eg, voluntary licensing) promote procurement of high-value essential cancer medicines on national formularies in the context of supporting sustainable health systems to achieve universal health coverage.